The problem of reliability of information in the information service (Questions asked in the contemporary information search) - Kazimi, Parviz Firudin Oqlu; Oqlu, Mammadov Mehmanali Akbar; Tofiq, Rzayeva Zahida (Technium Social Sciences Journal, 2021)
Specialists working in the global information space, as organizers and participants in information processes, become witnesses to the problems that arise in this space. The user has difficulty making the right decisions, especially in the event of a conflict of interest in the information space. In some cases, a "conflict of interest" leaves the consumer with a choice. Such cases are more common on social networks. The consumer of information sometimes participates in this information space as a distributor of information. In some cases, the user becomes a disseminator of disinformation because the reliability of the information is “in doubt”. In some cases, disinformation is more interesting because of its attractiveness. We also see an increase in the number of "products of disinformation" in the global information space. The article discusses a project aimed at resolving conflicts of interest in the global information space. Conflict of interest is a widespread problem in the global information space. Between "information monopolists" and the state, between sellers and consumers, between sources of information and consumers of information, etc. As a result of systematic discussions, it can be assumed that new approaches to the problem of conflicts of interest may appear that can contribute to "accelerating progress." In this regard, the idea that libraries are a reliable source of information, especially on global networks, is supported and encouraged. The purpose of the article is to analyze the features of a project aimed at solving the problem of conflict of interest, based on modeling within an integrated system and finding optimal solutions in the context of various corporate interests. This will exclude the manipulation of conflicts in the global network. The abundance and dynamics of information growth, the problem of the reliability of information products and attempts to manipulate the growing information products show that the problem of information reliability will remain relevant in the next 10-20 years.